Electron Backscatter Diffraction Analysis of the Microstructure Fineness in Pure Copper under Torsional Deformation - Wang, C.P.; Fan, J.K.; Li, F.G.; Liu, J.C. (Проблемы прочности, 2018)
Torsional deformation is regarded a promising deformation procedure to prepare the gradient structural materials. Pure copper was subjected to large plastic strains in torsion. Electron backscatter diffraction analysis was used to explore the microstructure evolution. The observations demonstrate that both high-angle grain boundaries and misorientation increase with strain. The grains finer and more homogeneous. In addition, the microstructure within the shear band demonstrates a distinct preferred orientation. The crystal <110> direction is parallel to the shear direction, and the crystal {111} inclines to the plane shear surface. A torsion-induced bar specimen includes a {011} <211> brass texture, {011} <100> Gaussian texture, and stronger {112} <111> copper texture.